UJI KAPASITAS ADSORPSI COCO PEAT UNTUK MENYISIHKAN DETERJEN DALAM LIMBAH CAIR DOMESTIK - Rizki Febriani, Karina
Nowadays, for removing organic pollutants, ammonia, detergents, odor and other micro-pollutants in drinking water and waste water, usually using processing by adsorption process using activated carbon powder, followed by the physics processing with coagulation, flocculation, sedimentation and disinfection with chlorine. With the high price of powdered activated carbon and chemicals for kogulan and flocculants, then the cost of drinking water treatment and wastewater into becoming more frequent. One way to consider is to look for an alternative adsorbent material for the decomposition of detergent compounds which may be used in drinking water treatment and wastewater using activated carbon addition. Research carried out by the method of batch adsorption, using coco peat adsorbent dosage of 2.8% dry weight in 300 ml of detergent solution with various concentration of 1 mg/L, 2 mg/L, 3 mg/L, 4 mg/L, and 5 mg/L. Samples of water were used, is tributary of Cikapundung river in RW 03 Kelurahan Dago and by creating a solution containing detergent powder detergent commercial. The process of adsorption is carried out at a time variation of the 10 minutes, 20 minutes, 40 minutes, 60 minutes and 120 minutes. After reaching equilibrium solution of the filtrate was taken and analyzed by the method of Methylene Blue Active Substances (MBAs). This study aims to determine the removal efficiency of coco peat at equilibrium conditions in the preliminary process of detergents in the wastewater. Detergent solution made by dissolving powdered detergent brands Rinso Anti Noda into distilled water with a detergent concentration of 100 mg/L then dilution to obtain detergent solution with a concentration of 1 mg/L, 2 mg/L, 3 mg/L, 4 mg/L, and 5 mg/L. The concentration of surfactant in tributary of Cikapundung river in RW 03 Kelurahan Dago is 0.11 mg/L MBAS. Because the concentration of surfactant in tributary of Cikapundung river RW 03 Kelurahan Dago was well below the standards, the water samples were used to test the adsorption artificial detergent solution. From the research, obtained the optimum adsorption contact time of 40 minutes with a removal efficiency of 54.825%. Coco peat adsorption capacity in the range of 0.011 to 0.127 mg/g and removal efficiency ranged from 30.79 to 70.88%. The mechanism of adsorption of the detergent by coco peat according to the Freundlich isotherm. This is because the value of R2 close to 1 so showed high compatibility between models with calculations adsorpsi. Based on the linear regression calculation Freundlich isotherm, the value of n is 0.308 and the value of k is 18.187.